2017
DOI: 10.3391/mbi.2017.8.4.12
|View full text |Cite
|
Sign up to set email alerts
|

Using dissolved carbon dioxide to alter the behavior of invasive round goby

Abstract: Experimental studies evaluating the effects of food availability on the movement of free-ranging animals generally involve food supplementation rather than suppression. Both approaches can yield similar insights, but we were interested in the potential for using food suppression for the management and control of invasive predators, in particular, the brown treesnake (Boiga irregularis) on Guam. However, understanding a species' response to food resources is critical before employing such a strategy. We studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…; Cupp et al. , ). One potential strategy to mitigate treatment avoidance would be to rapidly elevate CO 2 levels to the point where fish lose equilibrium and become heavily sedated.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…; Cupp et al. , ). One potential strategy to mitigate treatment avoidance would be to rapidly elevate CO 2 levels to the point where fish lose equilibrium and become heavily sedated.…”
Section: Discussionmentioning
confidence: 98%
“…For example, invasive Round Goby Neogobius melanostomus were observed losing equilibrium within minutes when exposed to >150 mg/L CO 2 (Cupp et al. ). Rapid influx of CO 2 across the blood–brain barrier results in a narcotic state where fish would be unable to physically relocate away from CO 2 piscicide treatments, and prolonged lethal exposure is imminent (Yoshikawa et al.…”
Section: Discussionmentioning
confidence: 99%
“…Progression through the strongest planes of anesthesia ultimately resulted in mortality for individuals at the highest concentrations (Figures 2 and 4, Tables 3 and 4). Fortunately, the exposure risk in management applications may be moderated by animal behavior because several studies have demonstrated that fish can sense and avoid areas with elevated CO 2 before the onset of severe physiological impairment (Donaldson et al 2016; Cupp et al 2017a, 2017b). Unlike animals in a natural environment, fish in the present study were confined within test tanks and did not have an opportunity to avoid CO 2 exposure Behavioral avoidance is an advantageous behavioral response for CO 2 as an invasive species deterrent barrier but could present challenges when administering CO 2 for lethal purposes because fish may avoid LCs if the treatment is not uniformly delivered.…”
Section: Discussionmentioning
confidence: 99%
“…), and Round Goby Neogobius melanostomus (Cupp et al. ). When deployed, CO 2 barriers could influence fish movements via two primary mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…; Cupp et al. ), allowing zones of CO 2 to (1) deter passage through a choke point as fish “choose” to swim to water with improved quality or (2) deflect organisms to a target area to facilitate harvest. Second, due to the anesthetic properties of CO 2 , if fish are forced to spend extended periods of time in elevated‐CO 2 zones—for example, if CO 2 is deployed in a confined space, such as a shipping lock—animals can lose equilibrium, and movement can be prevented.…”
Section: Discussionmentioning
confidence: 99%